Assessment of Spatial Diversity of the Potential of the Natural Environment in the Context of Sustainable Development of Poviats in Poland - Paweł Dziekański; Piotr Prus; Mansoor Maitah; Magdalena Wrońska (Energies, 2021)
The activities of the poviat are a combination of interrelated factors. The use of natural resources should be carried out in accordance with the principles of sustainable development. The aim of this research was to assess the spatial differentiation of development relationships, the natural environment, and ecology of poviats in Poland, using a synthetic measure. Empirical data were collected in the spatial terms of poviats in Poland. The choice of variables was conditioned by the availability of data of the Central Statistical Office for 2010–2019. The assessment of development of poviats indicates disproportions in terms of development variables, as well as the natural environment and ecology, and the existence of a weak impact of natural conditions for development. Poviats distinguished by a higher level of natural environment are not characterized by a higher measure of development. The reason for the low impact of non-financial conditions on the development of poviats is their dependence on transfer from the state budget and the amount of current expenditure. The results may constitute a source of information for local government authorities on the disproportions existing between units, on the determination of directions of development policy optimization in terms of the natural environment and ecology.